Deconstructing Beauty Standards: Unpad Geulis Instagram Account - At Thariq, Muhammad Wisnu Danang; Lesmana, Aditya Candra; Gunawan, Wahyu (Masyarakat: Jurnal Sosiologi, 2023)
This study aims to deconstruct the discourse of beauty standards represented by Unpad Geulis' Instagram account. Using Derrida's framework of deconstruction, the authors dismantle the text structure on Unpad Geulis' beauty standards, in the form of a slim body, clean, smooth face, white skin color and healthy hair as a dominative, hegemonic, and discriminative. Furthermore, the authors employ the reading of différance, to explore the possibility that Unpad Geulis' beauty standards would not exist without the marginalized beauty standards. Such a reading is done by reading horizontally the text structure of Unpad Geulis, to find a new meaning that was previously concealed. The study also indicates objectification and privacy violation of women, displayed on Unpad Geulis, which can affect women’s psychological well-being. Finally, deconstruction dissects the relationship between Unpad Geulis and Universitas Padjajaran (Unpad) as an educational institution, uncovering forms of aporia or contradictions in Unpad's cultural values.